Reproduction in the U.S., 1965 - Ryder, Norman B.; Westoff, Charles F. (Princeton, NJ : Princeton University Press, 2017)
The 1965 National Fertility Study is the third in a continuing series of major studies of American fertility. Based on interviews with 5,600 married women under the age of 55, the report is concerned with the measurement of all facets of reproductive behavior.Originally published in 1971.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.
Frontmatter -- Contents -- Chapter I. Background of the 1965 National Fertility Study -- Chapter II. Orientations Toward Numbers of Children -- Chapter III. The Trend of Expected Parity -- Chapter IV. Racial, Religious, and Socioeconomic Differences in Fertility -- Chapter V. Contraception -- Chapter VI. Use of the Pill -- Chapter VII. Some Effects of Pill Use -- Chapter VIII. Catholic Conformity Before and After the Papal Encyclical -- Chapter IX. Fertility Planning -- Chapter X. Attitudes Toward Abortion -- Chapter XI. Birth Intervals and Pregnancy Intervals -- Appendix A: Inconsistency of Response -- Appendix B: 1965 Questionnaire -- Appendix C: Related Publications -- Index
Mode of access: Internet via World Wide Web.
In English.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 08. Jul 2019)
Keywords: Birth control -- United States; Family size -- United States; Fertility, Human; SOCIAL SCIENCE / Sociology / General